Pameran Bisnis Ibu-Ibu Desa Glagaharum sebagai Upaya Meningkatkan Pendapatan untuk Mencapai Sustainable Development Goals (SDGs) - Santoso, Brian Timothy; Lainardy, Jesslyn Eunice; Tjioe, Vincentia Jennifer Evelyn; Sitepu, Sri Nathasya Br (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
Glagaharum Village is one of the villages in Porong District, Sidoarjo. Housewives of Glagaharum Village have high potential to improve their village's economy with their sewing skills. However, knowledge in calculating the cost of goods sold and marketing products effectively is still very minimal. Therefore, the "Kampung Jahit Arumpreneur" program is present as an effort to improve education and the economy of Glagaharum Village. Through training in the form of holding exhibitions, this program also contributes to realizing SDGs goals 1 and 4, namely poverty alleviation and quality education. The training in selling typical products of Glagaharum Village at Grand City Surabaya aims to sharpen the knowledge and skills of Glagaharum Village mothers to market and attract customers to compete in the market.